Association between breastfeeding duration and postpartum weight retention of lactating mothers: A meta-analysis of cohort studies. Issue 4 (August 2018) - Jiang, Mingjun; Gao, Haer; Vinyes-Pares, Gerard; Yu, Kai; Ma, Defu; Qin, Xueying; Wang, Peiyu
Summary: Background & aims: To clarify the relationship between different breastfeeding duration and postpartum weight retention through meta-analysis. Methods: In this study, all relevant studies that described the effect of breastfeeding duration on postpartum weight retention were identified from Pubmed, Cochrane, and WANGFANG databases and so on (1960–2016). This meta-analysis had been registered in International Prospective Register of Systematic Reviews (CRD42016038409). Results: Fourteen cohort studies involving 66 comparisons were included. Compared with bottle-feeding mothers, breastfeeding mothers had significantly lower postpartum weight retention of −0.38 kg (95% confidence interval: −0.64,  −0.11 kg). Subgroup analysis showed that, mothers who were primipara, less than 30 years old or normal pre-pregnancy body mass index had lower postpartum weight retention. When breastfeeding duration were stratified into <12 weeks, 12 weeks–24 weeks, 24 weeks–48 weeks, and ≥48 weeks, postpartum weight retention in breastfeeding women presented a U-shaped trend: a decline during early breastfeeding duration (year 1) (from 0.23 kg at < 12 weeks to −1.58 kg at 24–48 weeks) and then an increase in the follow-up duration (from −1.58 kg at 24–48 weeks to −0.97 kg at more than 48 weeks). Conclusions: Our results indicated that breastfeeding including exclusive breastfeeding and mixed breastfeeding were inversely related to postpartum weight retention. The decreasing influence of breastfeeding was more significant when the lactating mothers were less than 30 years old, primipara, normal pre-pregnant body mass index, or breastfeeding duration for 6–12 months.